The Chilean fiscal rule - Michael Pedersen (Danmarks Nationalbank, 2008)
From 2001 the fiscal policy in Chile has been based on a structural surplus rule. Under this rule, the government is committing itself to maintain its expenditures equal to the structural revenue minus the target for the structural surplus, which is expressed in terms of the GDP. The calculation of the structural balance depends on trend output, the long-run copper price and the structural income from Codelco's molybdenum sale. While the latter is calculated with a reference price determined as the average of past prices, panels of independent experts, who meet once a year, determine the two former. The fact that independent experts have substantial influence on the fiscal budget makes the Chilean fiscal rule different from similar rules applied in other countries. Compliance with the rule is not a legal obligation but a voluntary undertaking on the part of the government. Although the fiscal revenue has increased substantially in recent years due to a soaring copper price, the structural balance has remained stable at 1 % of the GDP. Hence, public saving has increased rapidly, accumulating in two sovereign wealth funds, which are administered by the Central Bank.
Keywords: 330; Finanzpolitik; Regelbindung; Haushaltsplanung; Öffentlicher Haushalt; Chile